2015
DOI: 10.1002/ccr3.341
|View full text |Cite
|
Sign up to set email alerts
|

Are de novo rea(21;21) chromosomes really de novo?

Abstract: Key Clinical MessageWe report a rare case of recurrent trisomy 21 caused by an isochromosome 21q and what is very likely to be maternal germ-line cell mosaicism. Over 90% of cases of rob(21;21) reported in the literature are due to an isochromosome 21q, with a risk of recurrence of more than 10%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Can it be that ECA26 is more prone for centric fusion than other equine small acrocentric chromosomes? Chromosome-specific effects have been observed in humans where a small percentage of cases of Down and Patau syndrome with trisomy HSA21 and HSA13, respectively, have the extra chromosome in the form of Robertsonian fusion or an isochromosome [ 15 , 16 , 17 , 35 , 36 ]. In Down syndrome, there are even rare mosaic cases where one cell line carries HSA21 isochromosome and another, a Robertsonian fusion [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Can it be that ECA26 is more prone for centric fusion than other equine small acrocentric chromosomes? Chromosome-specific effects have been observed in humans where a small percentage of cases of Down and Patau syndrome with trisomy HSA21 and HSA13, respectively, have the extra chromosome in the form of Robertsonian fusion or an isochromosome [ 15 , 16 , 17 , 35 , 36 ]. In Down syndrome, there are even rare mosaic cases where one cell line carries HSA21 isochromosome and another, a Robertsonian fusion [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In rare occasions, trisomies of acrocentric autosomes are combined with Robertsonian fusion or isochromosome formation [ 15 , 16 , 17 ], so that despite of aneuploidy, the diploid chromosome number remains normal. For example, about 5–6% of cases with Down syndrome carry unbalanced heterologous or homologous fusions involving HSA21 [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Herve et al 7 have reported a case of recurrent trisomy 21 caused by an isochromosome 21q {i(21q)} very likely secondary to a maternal germline cell mosaicism. They hypothesize that vast majority of apparently de novo cases of rea(21;21) may be due to an i(21q) with maternal or paternal inheritance.…”
Section: Discussionmentioning
confidence: 99%